The differential in vivo contribution of spinal α2A- and α2C-adrenoceptors in tonic and acute evoked nociception in the rat - López-Córdoba, Gustavo; Martínez-Lorenzana, Guadalupe; Lozano-Cuenca, Jair; Condés-Lara, Miguel; González-Hernández, Abimael (Frontiers in Pharmacology, 2022)
Spinal α2-adrenoceptor induces analgesia by neuronal inhibition of primary afferent fibers. This family receptor coupled to Gi/o proteins can be subdivided into three functional subtypes: α2A, α2B, and α2C-adrenoceptors, and current evidence on spinal analgesia supports the relevance of α2A and seems to exclude the role of α2B, but the functional contribution of α2C-adrenoceptors remains elusive. The present study was designed to pharmacologically dissect the contribution of spinal α2-adrenoceptor subtypes modulating tonic or acute peripheral nociception. Using male Wistar rats, we analyzed the effect of spinal clonidine (a non-selective α2A/α2B/α2C-adrenoceptor agonist) and/or selective subtype α2-adrenoceptor antagonists on: (i) tonic nociception induced by subcutaneous formalin (flinching behavior) or (ii) acute nociception induced by peripheral electrical stimulus in in vivo extracellular recordings of spinal dorsal horn second-order wide dynamic range (WDR) neurons. Clonidine inhibited the nocifensive behavior induced by formalin, an effect blocked by BRL 44408 (α2A-adrenoceptor antagonist) but not by imiloxan (α2B-adrenoceptor antagonist) or JP 1302 (α2C-adrenoceptor antagonist). Similarly, spinal BRL 44408 reversed the clonidine-induced inhibition of nociceptive WDR activity. Interestingly, spinal JP 1302 per se produced only behavioral antinociception (an effect blocked by bicuculline, a preferent GABAA channel blocker), but no correlation was found with the electrophysiological experiments. These data imply that, at the spinal level, (i) presynaptic α2A-adrenoceptor activation produces antinociception during acute or tonic nociceptive stimuli; and (ii) under tonic nociceptive (inflammatory) input, spinal α2C-adrenoceptors are pronociceptive, probably by the inactivation of GABAergic transmission. This result supports a differential role of α2A and α2C-adrenoceptors modulating nociception.